Pola Asuh Orang Tua dalam Meningkatkan Perkembangan Kecerdasan Emosional Anak Usia 12-15 Tahun di Lingkungan RT 14 Vila Tangerang Elok Kelurahan Kutajaya - Nisa, Dewi Nur Fajarotun; Haila, Hidayatullah; Siregar, Herlina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to identify parenting patterns in the development of emotional intelligence in children aged 12-15 years in the neighborhood of RT 14 Vila Tangerang Elok, Kutajaya District, and evaluate the results of parenting patterns in the development of emotional intelligence in children aged 12-15 years in the neighborhood of RT 14 Vila Tangerang Elok, Kutajaya Village, and analyzing the factors that influence parenting patterns in the development of emotional intelligence in children aged 12-15 years in the neighborhood of RT 14 Vila Tangerang Elok, Kutajaya Village. The method used in this research is descriptive with a qualitative approach. The data collection techniques used were observation, interviews, and documentation. The data sources obtained were 5 parents and 5 children. The results of this research show that the parenting pattern applied by parents about RT 14 Vila Tangerang Elok is a democratic parenting style where this parenting has developed well, although there are still children who are not able to control their emotions.